Using a Flexible Diary Method Rigorously and Sensitively With Family Carers. (June 2019) - Herron, Rachel; Dansereau, Lisette; Wrathall, Meghan; Funk, Laura; Spencer, Dale
Health and social science researchers are increasingly interested in the range of new possibilities and benefits associated with diary methods, particularly using digital devices. In this article, we explore how a flexible diary method, which enables participants to choose the device (i.e., paper notebook, tablet, or computer) and medium (i.e., text, photographs, sketches) through which they narrate their experiences, can be used to promote sensitive and rigorous research engagement with family carers to people with dementia. We used a diary interview method with 10 carers over the course of 6 weeks to explore how they experience and interpret the changing behaviors of their cognitively impaired kin. We reflect on how the quality of diary data can be enhanced alongside the ethical dimensions of research with carer populations, through different forms of diary keeping, regular interaction with participants, reflexive practice, and follow-up interviews.